2014
DOI: 10.1038/srep05462
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, plant colonization potential and phenanthrene degradation performance of the endophytic bacterium Pseudomonas sp. Ph6-gfp

Abstract: This investigation provides a novel method of endophyte-aided removal of polycyclic aromatic hydrocarbons (PAHs) from plant bodies. A phenanthrene-degrading endophytic bacterium Pseudomonas sp. Ph6 was isolated from clover (Trifolium pratense L.) grown in a PAH-contaminated site. After being marked with the GFP gene, the colonization and distribution of strain Ph6-gfp was directly visualized in plant roots, stems, and leaves for the first time. After ryegrass (Lolium multiflorum Lam.) roots inoculation, strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 50 publications
1
49
0
1
Order By: Relevance
“…Research of Sun et al, (2014) also confirmed that after ryegrass (Lolium multiflorum Lam.) roots inoculation, Pseudomonas sp.…”
Section: Effect Of Isolates On Root and Shoot Lengthsupporting
confidence: 53%
“…Research of Sun et al, (2014) also confirmed that after ryegrass (Lolium multiflorum Lam.) roots inoculation, Pseudomonas sp.…”
Section: Effect Of Isolates On Root and Shoot Lengthsupporting
confidence: 53%
“…GFP is a common reporter gene used to detect and quantify endophytic colonization in plant tissues (Timmusk et al 2005;Ji et al 2014;Sun et al 2014) with the primary assumption that it is just a detection tool and the basic metabolic characteristics of the strain are not affected by D r a f t tagging. In this study, our main objective was to determine if GFP-tagging of an endophytic diazotroph, P. polymyxa P2b-2R, could affect its ability to fix N 2 and promote plant growth when inoculated onto corn.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, P. polymyxa P2b-2R was tagged with green fluorescent protein (GFP) to determine the sites of endophytic colonization in lodgepole pine (Anand and Chanway 2013a). GFP has been extensively used in detecting internal tissue colonization by endophytic diazotrophs of various genera including Paenibacillus, Bacillus, Pseudomonas, and Azospirillum (Timmusk et al 2005;Rodriguez et al 2006;Ji et al 2014;Sun et al 2014). The fundamental assumption of GFP-tagging is that it only serves as a detection tool and that the basic metabolic characteristics of the bacterial strain do not change after tagging.…”
mentioning
confidence: 99%
“…Essa técnica tem sido amplamente utilizada para transformação de bactérias associadas à plantas (LACAVA et al, 2004;GAI et al, 2009;QUECINE et al, 2012;DOURADO et al, 2013;SUN et al, 2014), sendo assim adotada no presente estudo. Sendo que a SEMIA5079 apresentou um crescimento mais demorado, e a SEMIA5080 um crescimento mais rápido, atingindo a fase log às 40 h.a.i e às 8 h.a.i, respectivamente.…”
Section: Análise Do Efeito Da Transformação Com O Plasmídeo Pwm1013 Nunclassified